2016
DOI: 10.5688/ajpe80231
|View full text |Cite
|
Sign up to set email alerts
|

Student Performance in a Pharmacotherapy Oncology Module Before and After Flipping the Classroom

Abstract: Objective. To determine if a flipped classroom improved student examination performance in a pharmacotherapy oncology module. Design. Third-year pharmacy students in 2012 experienced the oncology module as interactive lectures with optional case studies as supplemental homework. In 2013, students experienced the same content in a primarily flipped classroom. Students were instructed to watch vodcasts (video podcasts) before inclass case studies but were not held accountable (ie, quizzed) for preclass preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 9 publications
2
60
1
3
Order By: Relevance
“…For instructors, the investments into digital pedagogy, which requires enormous time resources in additional to technical upskilling, might not produce a commensurate output in gained student performance. These findings were in line with other studies that observed no effects following the migration towards a flipped learning approach (Bossaer et al, ; Nishigawa et al, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For instructors, the investments into digital pedagogy, which requires enormous time resources in additional to technical upskilling, might not produce a commensurate output in gained student performance. These findings were in line with other studies that observed no effects following the migration towards a flipped learning approach (Bossaer et al, ; Nishigawa et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Mixed results were reported in four cases (Yestrebsky, ; Liebert, Lin, Mazer, Bereknyei, & Lau, ; Heyborne & Perret, ; Betihavas, Bridgman, Kornhaber, & Cross, ). A small number of cases reported no effect (Bossaer, Panus, Stewart, Hagemeier, & George, ; Nishigawa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The neutrality of student performance in ICM vs. traditional courses has been demonstrated in other disciplines outside of chiropractic, including pharmacy education, medical education, and nursing education. [14][15][16] In retrospect, the statement ''I possess the time management skills needed to be successful in this type of course format'' could have been presented either as an individual item and/or presented earlier in the survey, because of its contextual importance. Since time management skills is an indicator of student ''readiness'' for success in this type of course format, students' responses to this statement may have strongly influenced their responses to subsequent survey items.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been cited in health professional programs such as medicine, nursing, dentistry, and pharmacy [1][2][3][4][5][6][7]. Studies in these fields focus on student perception, satisfaction, and some on academic test scores.…”
Section: The Flipped Classroom In Health Professional Schoolsmentioning
confidence: 99%